2015
DOI: 10.1186/s13195-015-0143-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism and cerebrospinal fluid biomarkers profile of non-amnestic mild cognitive impairment in comparison to amnestic mild cognitive impairment and normal older subjects

Abstract: IntroductionMild cognitive impairment (MCI) is classically considered a transitional stage between normal aging and dementia. Non-amnestic MCI (naMCI) patients, however, typically demonstrate cognitive deficits other than memory decline. Furthermore, as a group, naMCI have a lower rate of an eventual dementia diagnosis as compared to amnestic subtypes of MCI (aMCI). Unfortunately, studies investigating biomarker profiles of naMCI are scarce. The study objective was to investigate the regional brain glucose met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
(70 reference statements)
0
26
0
2
Order By: Relevance
“…15,28 Coutinho and colleagues hypothesize that precuneus hypometabolism would be more specific for patients with aMCI, whereas additional frontal hypometabolism is associated with the non-aMCI subtype. 16 Although we cannot directly compare our findings with PET data, our results suggest structural network changes in patients with aMCI involve the precuneus, frontal, and temporal brain regions. Additional structural MRI investigations of non-aMCI patients would be necessary to differentiate brain changes across MCI subtypes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…15,28 Coutinho and colleagues hypothesize that precuneus hypometabolism would be more specific for patients with aMCI, whereas additional frontal hypometabolism is associated with the non-aMCI subtype. 16 Although we cannot directly compare our findings with PET data, our results suggest structural network changes in patients with aMCI involve the precuneus, frontal, and temporal brain regions. Additional structural MRI investigations of non-aMCI patients would be necessary to differentiate brain changes across MCI subtypes.…”
Section: Discussionmentioning
confidence: 67%
“…18 Positron-emission tomography studies demonstrate hypometabolic changes as well as a high susceptibility to amyloid deposition in the precuneus of patients with aMCI. [14][15][16] These changes are embedded into a network of metabolic alterations not only in medial temporal but also in frontal brain regions. 14,15,18 Using high-resolution MRI and whole-brain cortical thickness analyses, our aim was to investigate whether these network characteristics can be detected in structural brain imaging data as well.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with MCI have ~50% chance of progressing into AD dementia over 3-5 years and demonstrate impaired cerebral cortical glucose metabolism [3][4][5][6][7][8][9][10][11] and increased oxidative stress damage products [12]. These findings suggest an early impairment of bioenergetic function potentially arising from oxidative stress damage.…”
Section: Introductionmentioning
confidence: 76%
“…63 However, studies have shown that naMCI patients are more likely to have low Pittsburgh Compound B (PiB) retention and higher β-amyloid levels in the CSF. 64,65 It has also been shown that there are no significant differences in the hippocampal volume, cortical thickness, and hippocampal metabolism between amyloid-negative MCI patients and elderly controls, with the CSF levels of p-tau and t-tau being lower and the longitudinal cognitive performance being better in amyloid-negative MCI patients than in amyloid-positive MCI patients. 22,66 The finding of greater [ 18 F]THK5351 retention in the present aMCI group might have been due to a trend for greater amyloid positivity in that group compared to the naMCI group.…”
Section: Discussionmentioning
confidence: 99%